ChenYing-ning’s health thought research - Deng, Kunkun; Liang, Kangshuai (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Chen Chuining is a famous religious personage in modern and modern China, and a famous health expert. He is known as "fairy master" and "contemporary old gentleman" because of the health value brought by his fairy learning achievements. Mr. Chen Chuining wrote a work, which includes his lifelong perception of the theory and practice of health preservation, making health preservation a cultural treasure of all mankind. He is familiar with the traditional Chinese classics, understands the ancient and modern "mixed and versatile" health thought thoroughly, brings forth the new and takes the essence, and created the "fairy learning" health method from a unique perspective. He distinguished "xiology" from the traditional health ideas of medicine, Buddhism, Taoism, Confucianism and Wu, founded the Yangshan Half Monthly, broke the religious secret habits, and repeatedly verified the method and role of xiology health with scientific theory; advocated static therapy, Dan and other health concepts to promote people to prolong life and seek individual health care. Chen Chuining’s health thought not only enriches the connotation of the traditional Chinese health thought and the form of modern health practice, but also has a real and practical guiding significance for modern sports health and health care. Methods: Using literature data method, system analysis method and logic analysis method, follow the basic idea of "—— scientific analysis". First, starting with the policy text and the existing research results, the " Chen Shuining thought of health preservation and the public fitness information were comprehensively collected and collated. Secondly, the feasibility of Chen Chuanning’s health care guidance for the public fitness is analyzed from the multidisciplinary perspective of health care, sports and health care. Through the collection and analysis of Chen Funing’s health preservation thought system, we sort out a set of reliable and detailed theoretical basis, which has a profound influence and important theoretical value on modern health practice and mass fitness. Results: Health preservation is the essence of the traditional Chinese national culture. It has been more than two thousand years since Zhuangzi proposed it in the Warring States Period. China’s health culture has a long history, and has attracted the attention and research of many experts and scholars. Health preservation is the modern way of pursuing physical Corning health care, and it is a hot topic in the modern public fitness and health care industry. After the 2000 generation, Mr. Chen Chuining (1880-1969) cannot bear to see the traditional Chinese national culture erosion and infiltration by foreign culture, to awaken the people for the cognition and protection of traditional culture, traditional health culture as an independent discipline for research and advocacy, for modern health research and development laid a solid theoretical foundation, make health care conform to the trend of The Times. After the personal practice of "fairy learning" health, the body gradually improved. He more firmly believed that fairy learning health method has special effects on some diseases, which gave a high degree of affirmation that health can dispel disease, prolong age, prolong life, and enhance the body. At this point, Chen Chuining came up with the preliminary idea of fairy learning health, and then spent his life of intensive research, and eventually became a generation of famous artists. Conclusion: (1) Chen Chuining is a famous health preservation expert in modern and modern China. He has devoted himself to the academic excavation of health preservation all his life. He has spent his life and laid a solid theoretical foundation for the research and development of the perception and development of health preservation. ChenYing-ning’s health thought provides a theoretical basis worth reference and learning for the academic field, religious field and medical field of health preservation. (2) Chen Ying-ning’s health method is proven, is beneficial to the development of the physical, psychological, social adaptation of the health system. Among them, static work therapy, fetal rest, life double repair, inner Dan theory, female Dan practice and other health practice methods, suitable for the human body and mental health of the mass group, in line with the scientific nature of health rules. Chen Chuining health care method is to adapt to the social needs, to meet the modern pursuit of Corning health care, long vision of long life. (3) This paper reveals the mysterious veil of ChenYing-ning’s health preservation. Through the interpretation and analysis of ChenYing-ning’s health thought, it believes that the development of modern Chinese medicine, health concept and health practice are worth reference in ChenYing-ning’s health ideological system. Especially in the room surgery, Chen Shuining believes that natural desire, abstinence and can not help but desire, advocate double repair. In the practice of health preservation, Chen Chuining has promoted the development of medical treatment and health care, and enriched the ideological treasure house in the field of health preservation in China. (4) Chen Ying-ning’s comprehensive provides internal and external theory for modern fitness, static work therapy believes that static practice can solve physical, psychological, neurological diseases, in "sex", "life", that public fitness, health at the same time; and combined with the fetal breath, practice Dan, Yin and Yang harmony, to achieve the unity of man and man. ChenYing-ning’s health preservation thought in modern health preservation has a high promotion value and promotes the guiding significance of seeking disease removal and long observation and longevity. (5) Chen’s Ying-ning’s health ideas were influenced by the medical background, social environment and other related factors, there are research limitations and gaps, such as the old rules and secret, so that outsiders can not know their content; Chen’s letters and works, most are full of paper, ordinary people can not explain; no one publicly advocated Chen’s health ideas.